2021
DOI: 10.1080/03055698.2020.1867077
|View full text |Cite
|
Sign up to set email alerts
|

Literacy for life: evaluating the National Literacy Trust’s bespoke programme for schools

Abstract: This paper presents an evaluation of 'Literacy for Life' (LfL)a whole-school literacy programme, implemented in five secondary schools in England. The aims of LfL were to improve literacy attainment and to promote positive attitudes to reading and writing. However, when compared to other schools, there is little or no evidence that being in a LfL school, had any differential benefit for pupils' attainment. In LfL schools, the gap for disadvantaged pupils and those with SEN grew in the early years of the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Notably, LfL schools had considerable freedom around which elements they included in their programs. Morris et al (2021) adopted a quasiexperimental approach to compare outcomes in five secondary schools using the LfL program with "the strongest comparators available" (p. 7) (details of the control interventions were not provided). Contrary to expectation, the authors found reading enjoyment to decline slightly among participants across the three-year intervention.…”
Section: Reading and Literacy Skills Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, LfL schools had considerable freedom around which elements they included in their programs. Morris et al (2021) adopted a quasiexperimental approach to compare outcomes in five secondary schools using the LfL program with "the strongest comparators available" (p. 7) (details of the control interventions were not provided). Contrary to expectation, the authors found reading enjoyment to decline slightly among participants across the three-year intervention.…”
Section: Reading and Literacy Skills Programsmentioning
confidence: 99%
“…Of those eligible for inclusion in this review, positive effects on reading motivation and related outcomes (e.g., engagement, value, interest, curiosity) were identified in CORI (Guthrie and Klauda, 2014), LSC (Cantrell et al, 2012(Cantrell et al, , 2013, and PRJ (Vaden-Kiernan et al, 2012) implementation. However, improvements in reading motivation were not identified following LfL (Morris et al, 2021), and features of AR were identified as being potentially detrimental intrinsic motivation to read (Huang, 2012). This indicates that improvements in reading skills may not necessarily also map onto positive motivation outcomes.…”
Section: Reading and Literacy Skills Programsmentioning
confidence: 99%
“…any theoretical basis for the development of the PRJ programme, only that its potential effectiveness is "based on a small number of quasi-experimental studies" (p.3). Furthermore, Morris et al (2021) note the lack of a theory of change for the LfL programme as a potential explanation for its lack of effectiveness. The lack of clear or unified underlying theory of reading motivation change in adolescence provides a challenge for intervention implementation.…”
Section: Reading and Literacy Interventions Measuring Reading Motivat...mentioning
confidence: 99%
“…Indeed, Gilson et al (2018) have suggested that systematic motivational supports, where multiple facets of motivation are embedded throughout interventions, may be most effective in promoting motivation for reading. Notably however, it seems important that we are not trying to do 'too much' with a single intervention and that each element should have a theoretical and/or research backing (Morris et al 2021). Experimental work, particularly that which is guided by the specific needs of individual schools, groups and students, will be useful in developing an understanding of which elements of a multifaceted approach are likely to be most effective.…”
Section: Reading and Literacy Interventions Measuring Reading Motivat...mentioning
confidence: 99%
See 1 more Smart Citation